Penerapan Pendekatan SETS (Science Environment Technology And Society) untuk Meningkatkan Hasil Belajar IPA pada Materi Ciri-ciri Khusus Makhluk Hidup Siswa Kelas VI MIN I Kota Lhokseumawe - Hani, Farial (Yayasan Darul Hasanah Aceh, 2025)
This research was conducted as an effort to improve science learning activities and outcomes in the material of special characteristics of living beings through the application of the SETS (Science Environment Technology And Society) approach for class VI MIN I students in Lhokseumawe City for the 2019/2020 academic year. The subjects of this class action research are students of class VI MIN I Lhokseumawe City. The number of students is 32 students with 12 male students and 20 female students. This research was conducted within a period of 3 months, namely from September 2019 to November 2019 in the odd semester. Methodology This research is a class action research consisting of two cycles and each cycle consisting of two meetings. Each cycle consists of planning, executing actions and reflection. The research procedure consists of pre-research, one-cycle planning, one-cycle action execution, one-cycle observation, one-cycle reflection, two-cycle planning, two-cycle action execution, two-cycle observation and second-cycle reflection. The data collection technique is to collect test scores that are carried out at the end of each learning in each cycle using a question instrument (written test). Observation data is carried out by marking the number of students who are active in the learning process. The data are analyzed by means of percentage statistics. The results showed that there was an increase in the completeness of student learning outcomes from 40.62% in the pre-study increased to 65.62% in cycle I and increased to 87.50% in cycle II. The application of the SETS (Science Environment Technology And Society) Approach can improve the activities and learning outcomes of science learning in the material of special characteristics of living beings class VI MIN I Lhokseumawe City Academic year 2019/2020.